IMiD/CELMoD-induced growth suppression of adult T-cell leukemia/lymphoma cells via cereblon through downregulation of target proteins and their downstream effectors - Wang, Yu; Shimosaki, Shunsuke; Ikebe, Emi; Iha, Hidekatsu; Yamamoto, Jun-ichi; Fife, Nichole; Ichikawa, Tomonaga; Hori, Mitsuo; Ogata, Masao; Tsukamoto, Yoshiyuki; Hijiya, Naoki; Moriyama, Masatsugu; et al. (Frontiers in Oncology, 2024)
Adult T-cell leukemia (ATL) is an aggressive T-cell neoplasia associated with human T-cell leukemia virus type-1 (HTLV-1) infection and has an extremely poor prognosis. Lenalidomide (LEN, a secondgeneration immunomodulatory drug [IMiDs]) has been employed as an additional therapeutic option for ATL since 2017 but its mechanism of action has not been fully proved and recent studies reported emerging concerns about the development of second primary malignancies in patients treated with long term IMiDs therapy. Our purpose in this study is to elucidate the IMiDs mediated anti-ATL machineries. Thirteen ATL-related cell lines were divided into LEN-sensitive or -resistant groups. CRBN-knockdown (KD) led to a loss of LEN-efficacy and IKZF2-KD induced LEN-efficacy to resistant cells. DNA microarray analysis demonstrated distinct transcriptional alteration after LEN treatment between LEN-sensitive and -resistance ATL cell-lines. Oral treatment of LEN for ATL celltransplanted severe combined immunodeficiency (SCID) mice also indicated clear suppressive effects on tumor growth. Finally, a novel cereblon modulator (CELMoD), Iberdomide (IBE) exhibited broader and deeper spectrum of growth suppression to ATL cells with efficient IKZF2 degradation, which was not observed with other IMiDs treatments. Based on these findings, our study strongly supports the novel therapeutic advantages of IBE against aggressive and relapsed ATL.